2015
DOI: 10.20396/san.v18i2.8634682
|View full text |Cite
|
Sign up to set email alerts
|

Própolis e Segurança Alimentar

Abstract: A própolis é um material resinoso coletado de plantas e cascas de árvores pelas abelhas Apis mellifera, é dotada de substâncias biologicamente ativas com propriedades antioxidantes, anti-inflamatória, antitumoral e antimicrobiana. O objetivo desse trabalho consistiu em avaliar a segurança alimentar do uso da própolis na prevenção e no tratamento de doenças. O levantamento da literatura estudada foi feito de modo a abordar a relevância das propriedades terapêuticas da própolis através dos vários estudos científ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Due to propolis properties and growing consumer demand for ''green products'', and because their main constituents are considered GRAS (Burdock 1998;Luis-Villaroya et al 2015), propolis has gained popularity as a natural preservative for new applications in food and beverage production (Lacerda et al 2011;Moreira et al 2008). However, López et al (2015) alert for its safe user.…”
Section: Introductionmentioning
confidence: 99%
“…Due to propolis properties and growing consumer demand for ''green products'', and because their main constituents are considered GRAS (Burdock 1998;Luis-Villaroya et al 2015), propolis has gained popularity as a natural preservative for new applications in food and beverage production (Lacerda et al 2011;Moreira et al 2008). However, López et al (2015) alert for its safe user.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous results were obtained by Bertolin et al 2011, who evaluated TBA indices in dried salted pacu (Piaractus mesopotamicus), comparing samples containing BHT (10%) and samples containing phycocyanin (1.5%), and observed good antioxidant activity of phycocyanin, but which was not superior to that of BHT. Queiroz et al (1998) compared propolis extract (5%) and BHT (5%) in the preservation of bluefish (Pomatomus saltatrix) stored under refrigeration and found, on the 8th day of storage, 0.00 mg malonic aldehyde/g in the samples with propolis and 6.0 malonic aldehyde/g in those without antioxidant. The data corroborate the present study, where the TBA variable showed a similar response.…”
mentioning
confidence: 99%
“…The red propolis resulted in greater inhibition of lipid peroxidation and sequestration of free radicals when compared to antioxidants most commonly used in foods, such as BHA, BHT and TBHQ, which have aroused concern about their toxicity (Lacerda, Tiveron, & Alencar, ).…”
Section: Resultsmentioning
confidence: 99%